Age‐related off‐label drug prescribing in pediatric patients in South Korea and consistency of labeling compared to the United States, Europe, and Japan - Bojung Park; Hyesung Lee; Hyeyoung Choi; Jaehyun Lee (Wiley, 2024)
Abstract Insufficient labeling information regarding the appropriate age for prescribing drugs to the pediatric population is challenging. This study aimed to analyze the off‐label prescription of age‐related drugs for pediatric patients using claims data from South Korea and to assess the consistency of the approved age in South Korea, the United States, Europe, and Japan. In 2020, 1004 unique drugs were prescribed to the pediatric population in South Korea. We found that 641 drugs (63.8%, p < 0.0001) were related to off‐label prescriptions for age‐related use at least once, and the total number of off‐label prescriptions was 2,236,669 (62.2%, p < 0.0001). Chlorpheniramine (28%) was the most frequently prescribed drug for pediatric patients with an age‐related off‐label, followed by budesonide (9%) and epinephrine (9%). The degree of agreement in the approved age range for 641 off‐label drugs across countries was assessed using the overall kappa coefficient. We observed slight agreement in labeling across all countries (κ: 0.16, 95% confidence interval [CI]: 0.14-0.18). The highest degree of agreement was observed between the United States and Europe (0.41, 0.37-0.45) due to pediatric‐population‐specific legislation. South Korea showed the lowest degree of agreement with the United States and Europe (0.10, 0.06-0.14). The United States, Europe, and Japan showed fair agreement (0.23, 0.21-0.26). However, the degree of agreement between South Korea, the United States, and Japan (0.09, 0.06-0.11) and South Korea, Europe, and Japan (0.08, 0.05-0.10) was low. This study highlights the need for South Korean regulatory agencies to consider introducing pediatric legislation to prescribe evidence‐based drugs for safe and effective use.